GPS-BASED TRACKING IN ARMAPS: THE EFFECT OF DEGREE SLANT SMARTPHONE TO DISPLAY AUGMENTED REALITY OBJECTS - Anna Syahrani; Dede Wira Trise Putra; Aulia Rahma (Jurnal Teknik Informatika (Jutif), 2021)
This paper discusses the functionality testing of the augmented reality (AR) application, namely ARmaps. ARmaps is an AR application for directions that uses GPS-based tracking technology (GPS-based tracking). GPS-based tracking is one of the basic techniques in AR, which does not require special media to scan visual objects (marker-less) GPS-based tracking is used to display data digitally. Digital data displayed in the form of user location and directions. Based on the test results, it was found that there was an effect of the degree slant smartphone on the delay time in displaying 3D AR graphic objects. The test is done statically by adjusting the degree slant, namely acute, right-angle, and obtuse. Each test was carried out 30 times. Smartphones that support ARmaps performance should have an accelerometer, proximity, gyroscope, compass, A-GPS with Glonass and BDS sensors, as well as a camera. Smartphones that are placed with a large degree slant of 90o (obtuse angle) have a faster delay time in displaying 3D AR graphic objects, which is 12.7 seconds. This research becomes the basis for developing ARmaps as a guiding application (visualization guiding).